A series of drawings of a patient with schizophrenia-like psychosis associated with epilepsy: captured illustration of multifaced self-expression - Mandić Gajić, Gordana (Vojnosanitetski pregled, 2017)
Introduction. Drawings may give an insight into the complex mental process, however they have been underutilized in patients with psychosis associated with epilepsy. Case report. A 33-year-old, right handed female, diagnosed with schizophrenia-like psychosis associated with epilepsy, was treated in the Day Unit due to psychosocial rehabilitation. Besides other treatments, the patient underwent group analysis of drawings once a week. Qualitative analysis of the form and content of drawings made by free associations were performed. The varying of size and motives with vivid colours and the curve of perspective were documentated in three figures, followed by the last drawing which was without such elements. Conclusion. A series of drawings of patients with psychosis associated with epilepsy is needed to record a possible variations and disturbance of the immediate mental process. Group sessions may additionally contribute to diminish stigma and enhance psychosocial reintegration.